2017
DOI: 10.1055/s-0043-117180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Encapsulated Artemisia aucheri. L Magnetic Nanogel Extract on Shoulder Block in Rat

Abstract: The present study gave a proof of inducing a shoulder block in rat by IV injection administration of NIPAAM-MAA/Arthemisia aucheri. L extract complexes and magnet application to the shoulder. This will be a prospective formulation if a lower pH and temperature is considered for optimum release of this nanoanesthetics, thus, this can be translated into clinical practice for future applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previous history of the cause of back pain include; how the needles are inserted for spinal anesthesia, muscle strength presented, and risk factors for lower back pain [29]. Perhaps because women have less muscle mass, tendons becomes more flexible due to the presence of female sex hormones and lumbar lordosis, which accounts for more pain they are experiencing [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous history of the cause of back pain include; how the needles are inserted for spinal anesthesia, muscle strength presented, and risk factors for lower back pain [29]. Perhaps because women have less muscle mass, tendons becomes more flexible due to the presence of female sex hormones and lumbar lordosis, which accounts for more pain they are experiencing [30].…”
Section: Discussionmentioning
confidence: 99%
“…Gibofsky and colleagues also in their study, assessed the palliative efficiency and tolerability of low drug dose of diclofenac loaded on submicron particle capsules and celecoxib compared to placebo in patients suffering from moderate pain after surgery and in addition, lower-dose diclofenac loaded on submicron particle significantly decreased the overall pain intensity, compared to placebo after elective surgery [41]. All these reported studies imply that diclofenac loaded on submicron particle capsules are possible potential alternative treatment for patients experiencing pain [42].…”
Section: Nano-diclofenac and Chronic Painmentioning
confidence: 98%
“…A retrospective study by Butz et al, carried out on 90 patients with immediate implant-based breast reconstruction, showed that liposomal bupivacaine reduced patient visual analog pain scores in the immediate postoperative period, when compared with a bupivacaine pain pump and oral/ intravenous narcotic management of pain and decreased inpatient length of stay [56,57].…”
Section: Liposome Application In Pain Managementmentioning
confidence: 99%